Effects of irrigation temperature on heat control in vitro at different drilling depths - Sener, Bedrettin Cem; Dergin, Guhan; Gursoy, Bahar; Kelesoglu, Ergun; Slih, Imad (WILEY-BLACKWELL PUBLISHING, INC, 2009)
Thermal injury during implant bed preparation has a major influence on implant osseointegration and survival. This study investigated the effectiveness of the temperature of the saline solution used for heat control during drilling. Fresh frozen edentulous segments of bovine mandibles were sectioned into 12 x 6 cm pieces. Thermoresistors were placed 0.5 mm from the drilling cavity walls, at depths of 3, 7, and 12 mm. Signals from the three thermoresistors were analyzed using ORIGIN 5.0 software. The maximum temperatures during drilling without irrigation were 50.9, 47.4, and 38.1 degrees C at depths of 3, 7, and 12 mm, respectively. With irrigation using saline at 25 and 10 degrees C, the maximum temperatures at a depth of 12 mm were 37.4 and 36.3 degrees C, respectively. All other measurements with both 25 and 10 degrees C saline were below body temperature. This experimental in vitro study showed that more heat was generated in the superficial part of the drilling cavity than at the bottom. Therefore, external irrigation at room temperature can provide sufficient cooling during drilling. Lower temperature saline was more effective in cooling the bone, and irrigation of the site should be continued between the drilling steps. To cite this article:Effects of irrigation temperature on heat control in vitro at different drilling depths. Clin. Oral Impl. Res. 20, 2009; 294-298.doi: 10.1111/j.1600-0501.2008.01643.x.
Keywords: bone necrosis; drilling; implant; irrigation; BONE TISSUE; RABBIT; Dentistry, Oral Surgery & Medicine; Engineering